Association between atorvastatin exposure and low folate status: A case-Control study - Roberto Lozano; Irati Apesteguía; Alejandro Martínez (Wolters Kluwer Medknow Publications, 2022)
Objective: The objective of this study is to assess the association between exposure to atorvastatin (ATV) and low-plasma folate (PF) status. Methods: The sample consisted of patients admitted to the internal medicine service of a basic general hospital, located in Zaragoza (Spain). We adopted a pharmacoepidemiological case-control study design. For this, the number of treatment days (TDs) of all the drugs part of their treatment during the study period was obtained from each patient in the sample. The cases were comprised by the number of patient's TDs for which PF ≤3 mg/dl and the controls by the number of patient's TDs for which PF >3 mg/dl. To measure the strength of the association, the odds ratios (ORs) were calculated. The Chi-square test, using the Bonferroni correction, was used to calculate the statistical significance. Findings: The sample consisted of 640 polymedicated patients. The mean PF obtained were 8.0 ± 4.6 mg/dl and 2.1 ± 0.6 mg/dl, for the cases and controls, respectively; the total number of TDs for the cases and controls were 7615 and 57899, respectively. We obtained a U-shaped curve when representing the dose of ATV against the corresponding ORs when comparing cases with control. Conclusion: Exposure to ATV at 10 or 80 mg is associated with an augmented risk of low folate status. We recommend implementing guidelines for mandatory folic acid fortification in patients exposed to ATV doses of 10 or 80 mg.